The Research of Multimedia Complex Intelligent System in Financial Reporting Mode. (27th May 2022) - Li, Yanqin; Li, Xiaoping
Abstract : With the development of science and technology, in order to provide better financial information for economic decision-making, people urgently need a new financial reporting model. For the existing financial reporting model, it is only published in PDF or HTML format. This paper introduces multimedia technology and XBRL to reform, and studies the financial reporting model under the multimedia complex intelligent system, which can effectively remedy the drawbacks of the existing financial reporting model. Firstly, this paper introduces the theory and technical basis of the financial reporting model; secondly, according to the specific needs, it designs the relevant functions; finally, combined with multimedia technology and network technology, the financial reporting system under multimedia complex intelligent system is constructed. In addition, through testing the system implemented in this paper, the performance and functional practicability of the system are analyzed, which shows that the financial reporting system designed in this paper is suitable for today's economic environment and can provide financial information very well. When the number of process instances reaches 900 at the same time, the average flow cycle is only about 1.5 s.